POTENTIAL LEADING SECTOR TO DRIVE ECONOMIC GROWTH IN WEST NUSA TENGGARA PROVINCE - Iwan Harsono; Muhammad Dzul Fadlli; Muhamad Bai'ul Hak; Ali Akbar Hidayat (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
West Nusa Tenggara Province (NTB) has a small economy with a concentration of output to meet needs within its region and has a small proportion of trade outside the NTB region. Leading sectors are needed for faster economic growth. This study aims to describe how the structure of trade and the leading sectors drive economic growth. This research uses the descriptive quantitative method by utilizing interregional input and output data. The results indicate that the output trade structure is mostly traded within the NTB area and the majority is used for final demand. The sector with the largest output value in NTB is still the agricultural sector. However, based on sectoral linkages, the Electricity and Gas Procurement sector has the greatest capacity to encourage the progress of its upstream and downstream sectors. This means that the sector has the potential as a leading sector with the highest economic multiplier and should this sector be encouraged and continued to be spurred to boost economic growth.